A Student Information System Report: A Case Study of Kisoro Municipal Vocational Institute - Timothy Igiraneza (Uganda Christian University, 2024)
This report outlines the implementation of a Student Information System (SIS) at Kisoro Municipal Vocational Institute, aiming to modernize administrative processes and enhance communication channels. The SIS was designed to digitize student records, streamline administrative tasks, and improve data security. The implementation process involved needs assessment, vendor selection, customization, data migration, training, testing, and deployment. The SIS features are; Secure Login and Logout, Dashboard, Manage Department, Course Management, Student Information and Records Management, Manage User List (CRUD), Manage Account Details, and Manage System Information. Challenges such as resistance to change, technical issues, and data migration complexity were encountered during implementation. However, the SIS has had a significant impact, improving efficiency, transparency, data security, accessibility, and decision-making processes. Recommendations include continued training, continuous improvement, and integration with other systems. Overall, the SIS implementation has positively transformed institute operations and has been well received by stakeholders.